2009
DOI: 10.1089/gtmb.2008.0115
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR 677TT Alone and IRF6 820GG Together with MTHFR 677CT, but Not MTHFR A1298C, Are Risks for Nonsyndromic Cleft Lip with or without Cleft Palate in an Indian Population

Abstract: While MTHFR 677T homozygotes show a significant association with NSCL/P, heterozygotes 677CT are minor risk factors. MTHFR A1298C does not show a risk in any combination of alleles. IRF6 820GG too forms a minor risk. However, combined genotypes IRF6 GG/MTHFR 677CT together form greater risk for NSCL/P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 34 publications
3
28
0
Order By: Relevance
“…The region of India where the present study was conducted is health-impoverished even by Indian standards. Our previous case-control studies from the same region have shown rather low frequency of MTHFRC677T and A1298C in the control samples, but association as a risk factor with male infertility, cleft lip/palate and Down syndrome Rai et al, 2006;Ali et al, 2009). Therefore, in measuring tHcy, folic acid and vitamin B12, vis-à-vis the genotypes of the Hcy-pathway genes, our objective is to evaluate contribution of the individual variables (SNPs of Hcy-pathway genes) in the development of the phenotype (Hcy level), and to get an estimate of the relative contribution of environment (vitamins) in modulating the effect of genotypes in this region.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The region of India where the present study was conducted is health-impoverished even by Indian standards. Our previous case-control studies from the same region have shown rather low frequency of MTHFRC677T and A1298C in the control samples, but association as a risk factor with male infertility, cleft lip/palate and Down syndrome Rai et al, 2006;Ali et al, 2009). Therefore, in measuring tHcy, folic acid and vitamin B12, vis-à-vis the genotypes of the Hcy-pathway genes, our objective is to evaluate contribution of the individual variables (SNPs of Hcy-pathway genes) in the development of the phenotype (Hcy level), and to get an estimate of the relative contribution of environment (vitamins) in modulating the effect of genotypes in this region.…”
Section: Discussionmentioning
confidence: 84%
“…Case-control studies in our laboratory in populations from eastern regions of India show MTHFR SNPs, especially 677TT homozygosity, as a risk factor for male infertility , Down syndrome (Rai et al, 2006) and non-syndromic cleft lip ± palate (Ali et al, 2009). The C variant in MTHFR A1298C is also a risk factor though at a relatively low level.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Eleven articles were found to be eligible for the inclusion in the present meta-analysis Grunert et al, 2002;Shoteresuk et al, 2003;van Roij et al, 2003;Pezzetti et al, 2004;Mills et al, 2008;Ali et al, 2009;Sozen et al, 2009;Chorna et al, 2011;SemicJusufagic et al, 2012;Kumari et al, 2013). All these eleven studies were performed in different countries: Argentina , Germany (Grunert et al, 2002), India (Ali et al, 2009;Kumari et al, 2013), Ireland (Mills et al, 2008), Italy (Pezzetti et al, 2004), Netherlands (van Roij et al, 2003), Thailand (Shoteresuk et al, 2003), Ukraine (Chorna et al, 2011), and Venezuela (Sozen et al, 2009).…”
Section: Eligible Studiesmentioning
confidence: 99%
“…All these eleven studies were performed in different countries: Argentina , Germany (Grunert et al, 2002), India (Ali et al, 2009;Kumari et al, 2013), Ireland (Mills et al, 2008), Italy (Pezzetti et al, 2004), Netherlands (van Roij et al, 2003), Thailand (Shoteresuk et al, 2003), Ukraine (Chorna et al, 2011), and Venezuela (Sozen et al, 2009). In one study, Ali et al (2009) reported only allele numbers (Table 1).…”
Section: Eligible Studiesmentioning
confidence: 99%